Artificial intelligence based and digital twin enabled aeronautical AD-HOC network management - Bilen, Tuğçe (Graduate School, 2022)
The number of passengers using aircraft has been increasing gradually over the following years. With the increase in the number of passengers, significant changes in their needs have been made. In-flight connectivity (IFC) has become a crucial necessity for passengers with the evolving aeronautical technology. The passengers want to connect to the Internet without interruption regardless of their location and time. The aeronautical networks attract the attention of both industry and academia due to these reasons. Currently, satellite connectivity and air-to-ground (A2G) networks dominate existing IFC solutions. However, the high installation/equipment cost and latency of the satellites reduce their efficiency. Also, the terrestrial deployment of A2G stations reduces the coverage area, especially for remote flights over the ocean. One of the novel solutions is the Aeronautical Ad-hoc Networks (AANETs) to satisfy the IFC's huge demand by also solving the defects of satellite and A2G connectivities. The AANETs are based on creating air-to-air (A2A) links between airplanes and transmitting packets over these connections to enable IFC. The AANETs dramatically increase the Internet access rates of airplanes by widening the coverage area thanks to these established A2A links. However, the mobility and atmospheric effects on AANETs increase the A2A link breakages by leading to frequent aircraft replacement and reducing link quality. Accordingly, the mobility and atmospheric effects create the specific characteristics for AANETs. More specifically, the ultra-dynamic link characteristics of high-density airplanes create an unstructured and unstable topology in three-dimensional space for AANETs. To handle these specific characteristics, we first form a more stable, organized, and structured AANET topology. Then, we should continuously enable the sustainability and mapping of this created AANET topology by considering broken A2A links. Finally, we can route the packets over this formed, sustained, and mapped AANET topology. However, the above-explained AANET-specific characteristics restrict the applicability of conventional topology and routing management algorithms to AANET by increasing its complexity. More clearly, the AANET specific characteristics make its management challenging by reducing the packet delivery success of AANET with higher transfer delay. At that point, artificial intelligence (AI)-based solutions have been adapted to AANET to cope with the high management complexity by providing intelligent frameworks and architectures. Although AI-based management approaches are widely used in terrestrial networks, there is a lack of a comprehensive study that supports AI-based solutions for AANETs. Here, the AI-based AANET can take topology formation, sustainability, and routing management decisions in an automated fashion by considering its specific characteristics thanks to learning operations. Therefore, AI-based methodologies have an essential role in handling the management complexity of this hard-to-follow AANET environment as they support intelligent management architectures by also overcoming the drawbacks of conventional methodologies. On the other hand, these methodologies can increase the computational complexity of AANETs. At that point, we propose the utilization of the Digital Twin (DT) technology to handle computational complexity issues of AI-based methodologies. Based on these, in this thesis, we aim to propose an AI-based and DT-enabled management for AANETs. This system mainly consists of four main models as AANET Topology Formation Management, AANET Topology Sustainability Management, AANET Topology Mapping Management, and AANET Routing Management. Here, our first aim is to form a stable, organized, and structured AANET topology. Then, we will enable the sustainability of this formed topology. We also continuously map the formed and sustained AANET topology to airplanes. Finally, the packets of airplanes are routed on this formed, sustained, and mapped AANET topology. We will create these four models with different AI-based methodologies and combine all of them under the DT technology in the final step. In the Topology Formation Management, we will propose a three-phased topology formation model for AANETs based on unsupervised learning. The main reason for proposing an unsupervised learning-based algorithm is that we have independently located airplanes with unstructured characteristics in AANETs before forming the topology. They could be considered as the unlabeled training data for unsupervised learning. This management model utilizes the spatio-temporal locations of aircraft to create a more stable, organized, and structured AANET topology in the form of clusters. More clearly, the first phase corresponds to the aircraft clustering formation, and here, we aim to increase the AANET stability by creating spatially correlated clusters. The second phase consists of the A2A link determination for reducing the packet transfer delay. Finally, the cluster head selection increases the packet delivery ratio in AANET. In the Topology Sustainability Management, we will propose a learning vector quantization (LVQ) based topology sustainability model for AANETs based on supervised learning. The main reason for proposing a supervised learning-based algorithm is that we already have an AANET topology before the A2A link breakage, and we can use it in supervised learning for training. Accordingly, we can consider the clusters in AANET topology as a pattern; then, we can find the best matching cluster of an aircraft observing A2A link breakages through pattern classification instead of creating topology continuously. This management model works in three phases: winning cluster selection, intra-cluster link determination, and attribute update to increase the packet delivery ratio with reduced end-to-end latency. In the Topology Mapping Management, we will propose a gated recurrent unit (GRU) based topology mapping model for AANETs. In topology formation, we create AANET topology in the form of clusters by collecting airplanes having similar features under the same set. In topology sustainability, we sustain the formed clustered-AANET topology with supervised learning. However, these formed and sustained AANET topologies must be continuously mapped to the clustered airplanes to notify them about the current situation. This procedure could be considered a part of sustainability management. Here, we continuously notify the airplanes with GRU at each timestamp about topological changes. This management model works in two main parts ad forget and update gates. In Routing Management, we propose a q-learning (QLR) based routing management model for AANETs. For this aim, we map the AANET environment to reinforcement learning. Here, the QLR-based management model aims to let the airplanes find their routing path through exploration and exploitation. Accordingly, the routing algorithm can adapt to the dynamic conditions of AANETs. In this management model, we adapt the Bellman Equation to the AANET environment by proposing different methodologies for its related QLR components. Accordingly, this model mainly consists of two main parts current state & maximum state-action determination and dynamic reward determination. Therefore, we execute the topology formation, sustainability, and routing management modules through unsupervised, supervised, and reinforcement learning-based algorithms. Additionally, we take advantage of neural networks in topology mapping management. After managing the topology and routing of AANETs with AI-based models, in the DT-enabled AANET management, we will support them with the DT technology. The DT can virtually replicate the physical AANET components through closed-loop feedback in real-time to solve the computational challenges of AI-based methodologies. Therefore, we will introduce the utilization of DT technology for the AANET orchestration and propose a DT-enabled AANET (DT-AANET) management model. This model consists of the Physical AANET Twin and Controller, including the Digital AANET Twin with Operational Module. Here, the Digital AANET Twin virtually represents the physical environment. Also, the operational module executes the implemented AI-based models. Therefore, in this thesis, we aim to propose an AI-based and DT-enabled management for AANETs. In this management system, we will first aim to propose AI-based methodologies for AANET topology formation, topology sustainability, topology mapping, and routing issues. Then, we will support these AI-based methodologies with DT technology. This proposed complete management model increased the packet delivery success of AANETs with reduced end-to-end latency.
Yapay zeka tabanlı ve dijital ikiz destekli geçici havasal ağ yönetimi
Thesis(Ph.D.) -- Istanbul Technical University, Graduate School, 2022
Keywords: artificial intelligence; yapay zeka; aeronautical technology; havacılık teknolojisi